An earlier example of Portuguese concrete prefabrication, the "Torre da Boavista" condominium in Porto - Clara P. Vale (2014)
Prefabrication is a paradigm of the Modernity with a late and minor implementation in Portugal. The first large scale concrete prefabrication in Oporto takes place only in the 70's. Nuno Tasso de Sousa, a Portuguese architect influenced by the work of José Lluís Sert and by other international references designed a set of two buildings that apply a precast concrete slabs system on the facades' cladding. The absence of knowledge and technological skills leads to the use of the two buildings as a testing laboratory of design solutions, execution and assembly of panels, refined throughout the building phases. The designer company was a subsidiary of the building owner, a construction firm, fact that helped the relation between project and construction. The experience gained in these works ultimately lead to the creation of new company devoted to prefabrication that still exists today, and has work done in several countries. The objective of the study was to analyse the construction processes of these two building, its constructive characterization, mainly related to the facade elements and connections system, identifying differences between phases. Both the architect and the general contractor are still alive and in work practice so they were valuable sources of information along with the building and its building permit process. This Portuguese pioneering example, developed with "craftwork" solutions that still are in good conditions after 40 years, is an example of a durable mixed high-low-tech solution, with low cost and good long-term behaviour.